An inhibitory role for human CD96 endodomain in T Cell anti-tumor responses - Wang, Chelsia Qiuxia (2023)
Immune checkpoint blockade (ICB) therapy involves the inhibition of immune checkpoint regulators which reverses their limitation of T cell anti-tumor responses and results in long-lasting tumor regression. However, poor clinical response or tumor relapse was observed in some patients receiving such therapy administered via antibodies blocking the cytotoxic T lymphocyte-associated protein 4 (CTLA-4) or the programmed cell death 1 (PD-1) pathway alone or in combination, suggesting the involvement of additional immune checkpoints. CD96, a possible immune checkpoint, was previously shown to suppress natural killer (NK) cell anti-tumor activity but its role in human T cells remains controversial. Here, we demonstrate that CRISPR/Cas9-based deletion of CD96 in human T cells enhanced their killing of leukemia cells in vitro. T cells engineered with a chimeric antigen receptor (CAR) comprising human epidermal growth factor receptor 2 (EGFR2/HER2)-binding extracellular region and intracellular regions of CD96 and CD3ζ (4D5-96z CAR-T cells) were less effective in suppressing the growth of HER2-expressing tumor cells in vitro and in vivo compared with counterparts bearing CAR that lacked CD96 endodomain (4D5-z CAR-T cells). Together, our findings implicate a role for CD96 endodomain in attenuating T cell cytotoxicity and support combination tumor immunotherapy targeting multiple rather than single immune checkpoints.